Successful maternal outcome after vaginal delivery in a patient with Eisenmenger Syndrome - Chauhan, Divya; Agarwal, Rachna; Gupta, Prerna; Radhakrishnan, Gita; Radhika, Ayalur Gopalakrishnan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Patients with Eisenmenger syndrome are advised against pregnancy. Sometimes patients are diagnosed with Eisenmenger syndrome for the first time during pregnancy. This is what has happened in our case. A primigravida was diagnosed with ventricular septal defect with severe pulmonary artery hypertension for the first time during pregnancy at 34 weeks period of gestation. Management of such patients is challenging with different studies showing variable results. Here we describe such a case which was managed conservatively and was allowed to go into labour spontaneously with vacuum extraction during second stage which subsequently led to a favourable maternal outcome.